Indonesia dalam Meningkatkan Inklusi Keuangan - Irwandi, Irwandi (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2025)
This study aims to analyze the role of Islamic banking in increasing financial inclusion in Indonesia through microfinance products such as murabahah, ijarah, and qardhul hasan financing. With a descriptive qualitative approach, data were collected through literature studies and documentation from OJK, BI reports, and official publications of Islamic banks. The results of the study indicate that Islamic microfinance is able to reach unbankable communities, especially MSMEs. However, challenges in the form of lack of Islamic financial literacy and limited reach of digital services are still major obstacles. This study recommends strengthening Islamic financial education strategies and digitalization of services to support sustainable financial inclusion.